Complexation thermodynamics of α-cyclodextrin with ionic surfactants in water - Ondo, Daniel; Costas, Miguel (Journal of colloid and interface science, 2017)
The interaction of α-cyclodextrin (α-CD) with ten ionic surfactants (S) in water was systematically examined using isothermal titration calorimetry. The S comprised cationic and anionic head groups while the hydrocarbon alkyl chain length varied from eight to fourteen carbon atoms. The heat data were measured at five temperatures ranging from 283.15K to 318.15K and were treated simultaneously allowing the estimation of a thermodynamically consistent temperature dependence of the equilibrium constant, as well as the enthalpy and heat capacity for the sequential formation of the [α-CD·S] and the [α-CD2·S] inclusion complexes. All attempts to fit the data assuming that only [α-CD·S] complexes are present failed. It was found that the thermodynamic footprint of the [α-CD·S] complexes does not depend importantly on the head group, while the formation and stabilization of the [α-CD2·S] complexes is strongly influenced by the chemical nature of the polar head group. Several contributions to the thermodynamic parameters are discussed in detail. Among the studied surfactants, the decyl- and octylsulfates were identified as those with a predominant content of [α-CD2·S] complexes and hence they are promising candidates to form viscoelastic films at the liquid/air interface, as it was found previously for the dodecylsulfate surfactant.
Keywords: Inclusion complex; Isothermal titration calorimetry; Thermodynamic; Surfactant; -Cyclodextrin; Complexation